Students' Capability in Writing Descriptive Text of the Second Grade Students of SMP Muhammadiyah 8 Surakarta - Ismiyati, Ida, Aryati Prasetyarini, S.Pd, M.Pd, Nur Hidayat, S.Pd., M.Pd (2015)
This research aims to describe the students' capability of writing descriptive text, to identify the problem faced by the students in writing descriptive text and to identify the cause of the problem faced by the students in writing descriptive text at the second grade of SMP Muhammadiyah 8 Surakarta. The methods of collecting data is documentation and interview. The technique of data analysis is to answer the students' are capability in writing descriptive text is analytic scoring. The researcher analyzed the students' writing based on (a) content of the composition, (b) organization of the paragraph, (c) Grammar, (d) Vocabulary, and (e) mechanic The result shows that there are 3,12 % or 1 student categorized as excellence grade. There are 9,37% or 3 students categorized having as good grade. There are 68,75% or 22 students categorized as fair grade. There are 18,75% or 6 students categorized as poor grade. The problem faced by the students in writing are (1) Having limited number of vocab, (2) Poor grammar mastery, (3)Poor capability using diction. The causes of problem faced are (1) Problems in their interest of learning English language, (2) Problems with conveying the descriptive text from the teacher. Keyword: students' capability, writing, descriptive text